Experimental study on the glass fiber/waste cotton fabric-reinforced hybrid composites: Mechanical and rheological investigations. (September 2017) - Bodur, Mehmet S; Bakkal, Mustafa; Englund, Karl
In this work, the effect of hybridization on the mechanical and rheological properties of the glass fiber/waste cotton fabric-reinforced hybrid composites was investigated. For this purpose, glass fibers in different ratios of 2.5, 5, and 10 wt.% were added to the polymer composites with cotton fibers at the ratios of 12.5 and 25 wt.%. In order to have better interfacial bonding and to increase the effectiveness of glass fiber on the mechanical properties, maleic anhydride coupling agent was added to the hybrid composite samples. At the end of the study, the best ratios of maleic anhydride, cotton, and glass fiber for this kind composites were explored with respect to the economical and mechanical concerns. This study suggests that hybridization can be considered as most promising way to improve the mechanical properties for this novel composite material.